2014
DOI: 10.1038/nmat3973
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization switching through giant spin–orbit torque in a magnetically doped topological insulator heterostructure

Abstract: Recent demonstrations of magnetization switching induced by in-plane current in heavy metal/ferromagnetic heterostructures (HMFHs) have drawn great attention to spin torques arising from large spin-orbit coupling (SOC). Given the intrinsic strong SOC, topological insulators (TIs) are expected to be promising candidates for exploring spin-orbit torque (SOT)-related physics. Here we demonstrate experimentally the magnetization switching through giant SOT induced by an in-plane current in a chromium-doped TI bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
746
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 860 publications
(778 citation statements)
references
References 37 publications
16
746
4
Order By: Relevance
“…Since the as-cleaved data showed no enhancement of T C at the surface, the apparent differing values given by TEY and FY likely arise from the short ranged exchange interaction with the ferromagnetic Co overlayer. This finding can be useful for the development of new physical models of Cr-doped Bi 2 Se 3 and their use in, e.g., spintronic devices [6].…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Since the as-cleaved data showed no enhancement of T C at the surface, the apparent differing values given by TEY and FY likely arise from the short ranged exchange interaction with the ferromagnetic Co overlayer. This finding can be useful for the development of new physical models of Cr-doped Bi 2 Se 3 and their use in, e.g., spintronic devices [6].…”
mentioning
confidence: 78%
“…Magnetically doped TIs are host to a wide variety of exotic physical effects, perhaps most notably the recently confirmed quantum anomalous Hall effect (QAHE) [4], which requires the breaking of the TRS through the opening of a gap around the Dirac point [5]. Furthermore, such magnetically doped TIs offer extremely high spin-orbit torques, indicating great potential for spintronic devices [6].…”
mentioning
confidence: 99%
“…Popular approaches include passing a spin current through the soft layer to generate a spin transfer torque [2][3][4][5][6][7] or spin orbit torque [8][9][10][11] or domain wall motion [12][13] . Other approaches involve using voltage controlled magnetic anisotropy 14 , magnetoelectric effects [15][16][17] , magnetoionic effects 18 and magnetoelastic effects [19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%
“…6−9 Recent studies have shown a giant spin−orbit torque in TI originating from the strong spin− orbit interaction, 10,11 which enabled the current-induced magnetization switching through spin-transfer torque with a low current density. The unique feature of 3D TI, for instance, is that it has both insulating bulk and gapless Dirac surface states.…”
mentioning
confidence: 99%